Chronic NSAID use and long-term decline of renal function in a prospective rheumatoid arthritis cohort study. Issue 4 (19th December 2013) - Möller, Burkhard; Pruijm, Menno; Adler, Sabine; Scherer, Almut; Villiger, Peter M; Finckh, Axel; ,
Abstract : Objectives: Non-steroidal anti-inflammatory drugs (NSAIDs) may cause kidney damage. This study assessed the impact of prolonged NSAID exposure on renal function in a large rheumatoid arthritis (RA) patient cohort. Methods: Renal function was prospectively followed between 1996 and 2007 in 4101 RA patients with multilevel mixed models for longitudinal data over a mean period of 3.2 years. Among the 2739 'NSAID users' were 1290 patients treated with cyclooxygenase type 2 selective NSAIDs, while 1362 subjects were 'NSAID naive'. Primary outcome was the estimated glomerular filtration rate according to the Cockroft–Gault formula (eGFRCG ), and secondary the Modification of Diet in Renal Disease and Chronic Kidney Disease Epidemiology Collaboration formula equations and serum creatinine concentrations. In sensitivity analyses, NSAID dosing effects were compared for patients with NSAID registration in ≤/>50%, ≤/>80% or ≤/>90% of assessments. Findings: In patients with baseline eGFRCG >30 mL/min, eGFRCG evolved without significant differences over time between 'NSAID users' (mean change in eGFRCG −0.87 mL/min/year, 95% CI −1.15 to −0.59) and 'NSAID naive' (−0.67 mL/min/year, 95% CI −1.26 to −0.09, p=0.63). In a multivariate Cox regression analysis adjusted for significant confounders age, sex, body mass index, arterial hypertension, heart disease and for other insignificant factors, NSAIDs were an independent predictor for accelerated renal function decline only in patients with advanced baseline renal impairment (eGFRCG <30 mL/min). Analyses with secondary outcomes and sensitivity analyses confirmed these results. Conclusions: NSAIDs had no negative impact on renal function estimates but in patients with advanced renal impairment.